The Roles of Mesenchymal Stem Cells in Gastrointestinal Cancers - Xiang, Ze; Hua, Menglu; Hao, Zhou; Biao, Huang; Zhu, Chaojie; Zhai, Guanghua; Wu, Jian (Frontiers in Immunology, 2022)
Mesenchymal stem cells (MSCs) were reported to have strong immunomodulatory ability, and inhibit the proliferation of T cells and their immune response through cell-to-cell interactions and the generation of cytokines. With high differentiation potential and self-renewal ability, MSCs are considered to function in alleviating inflammatory responses, promoting tissue regeneration and inhibiting tissue fibrosis formation. As the most common malignancies, gastrointestinal (GI) cancers have high incidence and mortality. The accurate diagnosis, exact prognosis and treatment of GI cancers have always been a hot topic. Therefore, the potential applications of MSCs in terms of GI cancers are receiving more and more attention. Recently, there is increasing evidence that MSCs may serve as a key point in the growth, metastasis, inhibition, treatment and prognosis of GI cancers. In this review, we summarized the roles of MSCs in GI cancers, mainly focusing on esophageal cancer (EC), gastric cancer (GC), liver cancer (LC), colorectal cancer (CRC) and pancreatic cancer. Besides, we proposed MSCs as potential targets and treatment strategies for the effective treatment of GI cancers, which may provide better guidance for the clinical treatment of GI cancers.